PENGETAHUAN, SIKAP DAN EFEK SAMPING KEMOTERAPI PADA PASIEN DENGAN KANKER PAYUDARA - Dewi Marianthi; Nurhayati Nurhayati; Afdhal Afdhal; Muizzatul A’la (Journal Keperawatan, 2023)
Knowledge and attitudes about breast cancer are very important and have a big influence on the treatment and side effects of chemotherapy felt by breast cancer patients. The purpose of this study was to determine the relationship between knowledge and attitudes with chemotherapy side effects felt by breast cancer patients in Banda Aceh City in 2021. The method of this study was cross-sectional. Sampling using purposive sampling technique amounted to 43 breast cancer patients undergoing chemotherapy. Data collection from 27 April 2021 to 21 May 2021 using a standard questionnaire adopted from BMC Woman's Health in 2019 and the Breast Cancer Module: QLQ-BR23 questionnaire. Data analysis using chi-square. The results showed that the respondent's knowledge was in the moderate category (51.2%), the respondent's attitude was in the positive category (97.3%), and the perceived side effects of chemotherapy were in the mild category (88.4%). From the bivariate results, it was found that there was a relationship between knowledge of p value (P = 0.001) and attitude (P = 0.032) with chemotherapy side effects felt by breast cancer patients. It is hoped that patients with a medical diagnosis of breast cancer can deepen their knowledge about the treatment to be undertaken such as chemotherapy, so that the effectiveness of the treatment runs smoothly and all side effects of treatment can be passed properly.